Can we afford to grow older? : a perspective on the economics of aging - Disney, Richard (MIT Press, 1996)
This book is concerned with the economic consequences of the dramatic current and prospective demographic changes that are occurring in Western industrialized countries. There are chapters on the dependency burden aspects of Social Security programs and intergenerational redistribution; overlapping-generations models, feasible pension schemes, and aging populations; Social Security: paying for past pension promises; private pension plans in the demographic transition; productivity, wages, and educational attainment: the impact of workforce aging; retirement: the labor supply of older workers in an aging society; consumption and saving: life-cycle behavior and population aging; financing health care; and a public-choice perspective.